Jesus and the Samaritan woman (John 4:1-42) : a paradigmatic encounter for discipleship [μαθητής] and witness [μαρτυρία] - Smuts, Ricardo (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.